An anti-overturn Janus sponge with excellent floating stability for simultaneous pollutant remediation and oil/water separation. Issue 34 (11th July 2018) - Lee, Yo Seph; Kaang, Byung Kwon; Han, Nara; Lee, Ha-Jin; Choi, Won San
Abstract : This paper reports an anti-overturn Janus sponge that can absorb oil under harsh conditions such as high waves and strong winds, remediate pollutants in three liquid multiphases, and successively separate and remediate three liquid layers (light oil/water/heavy oil). Abstract : An anti-overturn Janus sponge (AJS) that partially floats/is partially submerged on/under water was prepared. The Janus characteristics originate from the cooperative effect of the hydrophilic part absorbing water and the hydrophobic part generating buoyancy. The AJS with an appropriate hydrophilic/hydrophobic ratio showed excellent floating stability under high waves and strong winds. The AJS also exhibited high adsorption of aqueous pollutants during fast oil/water separation due to its Janus characteristics, stably remained at the oil/water and water/oil interfaces in three liquid multiphases and removed aqueous pollutants at each interface. Because of its great control over the alteration of the ratio, structure, and shape of its hydrophilic and hydrophobic parts, the AJS can be transformed into various types of structures on demand. A pant-like structure that was divided into two branches could successively separate three liquid multiphases (light oil/water/heavy oil) and quickly purify contaminated water during the separation.